2016
DOI: 10.1002/anie.201606185
|View full text |Cite
|
Sign up to set email alerts
|

Complete Transmetalation in a Metal–Organic Framework by Metal Ion Metathesis in a Single Crystal for Selective Sensing of Phosphate Ions in Aqueous Media

Abstract: A complete transmetalation has been achieved on a barium metal-organic framework (MOF), leading to the isolation of a new Tb-MOF in a single-crystal (SC) to single-crystal (SC) fashion. It leads to the transformation of an anionic framework with cations in the pore to one that is neutral. The mechanistic studies proposed a core-shell metal exchange through dissociation of metal-ligand bonds. This Tb-MOF exhibits enhanced photoluminescence and acts as a selective sensor for phosphate anion in aqueous medium. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
64
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 148 publications
(65 citation statements)
references
References 48 publications
1
64
0
Order By: Relevance
“…Moreover, compared to amorphous materials, the highly ordered crystalline nature of MOFs allows for precise structural determinations and specific knowledge of structural changes that occur during the detection of an analyte and the detail sensing mechanism. To date, a wide range of luminescent MOFs, particularly lanthanide‐based MOFs, have been realized and reported as sensors for ions, small molecules, gas/vapors, temperature, pH values, and moisture …”
Section: Functionalization Of Mofs For Photoluminescent Tuning and Sementioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, compared to amorphous materials, the highly ordered crystalline nature of MOFs allows for precise structural determinations and specific knowledge of structural changes that occur during the detection of an analyte and the detail sensing mechanism. To date, a wide range of luminescent MOFs, particularly lanthanide‐based MOFs, have been realized and reported as sensors for ions, small molecules, gas/vapors, temperature, pH values, and moisture …”
Section: Functionalization Of Mofs For Photoluminescent Tuning and Sementioning
confidence: 99%
“…Utilizing luminescent MOFs as a platform for sensing anions has been investigated in the past decade. To detect F − , Chen et al reported the luminescent MOF‐76 to selectively sense F − based on a luminescence enhancement effect, and two other luminescent Ln‐MOFs sensors (Ln 2 (BPDC)(BDC) 2 (H 2 O) 2 ) n and Eu 3+ @Al(OH)(H 2 btec)·H 2 O), which were reported by Zhou et al and Hao et al, showed quenching responses to F − .…”
Section: Functionalization Of Mofs For Photoluminescent Tuning and Sementioning
confidence: 99%
See 1 more Smart Citation
“…Transmetalation of crystalline coordination polymers (CCPs, denoted as metal-organic frameworks (MOFs) in a more limited sense) has recently attracted significant attention because it opens up a very broad strategy for the synthesis of MOF or CCP materials that exhibit new chemical functionalities. [1][2][3][4] The incorporation of a new chemical functionality can be achieved via transmetalation, for example, high catalytic and redox activities may be accomplished that are otherwise unattainable de novo; [5][6][7] further, a fluorescent signal change is useful for ion detection when fluorescent metals are included. [8][9][10] The chemical equation of transmetalation, M nþ 1 ) * M nþ 2 , appears to be simple, indicating an uncomplicated phenomenon.…”
Section: Introductionmentioning
confidence: 99%
“…As a new type of luminescent material, lanthanide metal‐organic frameworks (Ln‐MOFs) provide an effective platform for chemical recognition by virtue of both the excellent, stimuli‐responsive photoluminescent characteristics of lanthanides through an “antenna effect” and the guest‐binding abilities of MOFs for analytes pre‐concentration . Indeed, considerable progress has been made in exploring Ln‐MOFs as luminescent sensors to detect various species and conditions, such as ions, organic small molecules/VOCs, gases, explosives, antibiotics, humidity, and temperature . Nevertheless, few studies on exploiting such materials for assessing DNA damage or 8‐oxo‐dG levels have been reported thus far, and the multimodal MOF‐based assay for a specific analyte is also particularly rare.…”
Section: Introductionmentioning
confidence: 99%